The importance of understanding different management paradigms in today's global economy. (4th March 2008) - Wickramasinghe, N.; Bali, R.K.; Naguib, R.N.G.; Dwivedi, A.
Merely recognising the existence of international management philosophies (e.g. Indian, Chinese, and Japanese) does not guarantee success in the workplace, conversely ignoring them may cause managerial problems which in turn is likely to significantly impair the development of a learning organisation. With globalisation in mind, this paper focuses on the futuristic learning organisation and attempts to analyse how the 21st century organisation would react to diverse management cultures. In light of the fact that a central aspect of the current knowledge economy is the need to develop Learning Organisations, a meta level framework is provided. This framework highlights that in learning organisations not only essential to foster Knowledge Management (KM) tools and strategies, but also to recognise that these KM drivers and facilitators are significantly moderated by culture and management style. In order to explore differing managerial styles in detail, this papers also presents a model that enables different management philosophies (i.e. Western, Chinese, Indian, Japanese management, and the Overseas Chinese Network) to be positioned against a key of common factors. From this model recommendations are made to facilitate the adoption of the appropriate managerial style to support effective operations and the transition to a learning organisation.